Unraveling the complex maternal history of Southern African Khoisan populations. Issue 3 (9th December 2013) - Barbieri, Chiara; Güldemann, Tom; Naumann, Christfried; Gerlach, Linda; Berthold, Falko; Nakagawa, Hirosi; Mpoloka, Sununguko W.; Stoneking, Mark; Pakendorf, Brigitte
ABSTRACT The Khoisan populations of southern Africa are known to harbor some of the deepest‐rooting lineages of human mtDNA; however, their relationships are as yet poorly understood. Here, we report the results of analyses of complete mtDNA genome sequences from nearly 700 individuals representing 26 populations of southern Africa who speak diverse Khoisan and Bantu languages. Our data reveal a multilayered history of the indigenous populations of southern Africa, who are likely to be the result of admixture of different genetic substrates, such as resident forager populations and pre‐Bantu pastoralists from East Africa. We find high levels of genetic differentiation of the Khoisan populations, which can be explained by the effect of drift together with a partial uxorilocal/multilocal residence pattern. Furthermore, there is evidence of extensive contact, not only between geographically proximate groups, but also across wider areas. The results of this contact, which may have played a role in the diffusion of common cultural and linguistic features, are especially evident in the Khoisan populations of the central Kalahari. Am J Phys Anthropol 153:435–448, 2014. © 2013 Wiley Periodicals, Inc.